Kinerja Direktorat Jenderal Bina Pembangunan Daerah Dalam Pengelolaan Sistem Informasi Monitoring Data Internal (e-SIMDATIN) di Kementerian Dalam Negeri Republik Indonesia - Prasetyo, Bagus Eko; Sinurat , Marja; Tahir , Baharudin (UIR Press, 2024)
The e-Simdatin application is an important instrument in accelerating access to information, simplifying the data collection process, facilitating analysis and decision making related to regional development. This research aims to describe, analyze and determine the performance of the Directorate General of Regional Development in Managing the Internal Data Monitoring Information System (e-Simdatin) including supporting and inhibiting factors as well as efforts in implementing activities. The research method used was descriptive qualitative research using 12 informants determined by purposive sampling. The theory used in this research uses the theory of Sinurat and Panjaitan (2017:173) which consists of 5 dimensions. Data collection uses interview, observation, documentation and triangulation techniques. Based on data analysis and discussion according to the dimensions of input, activities, output (output), results (outcome), impact (impact) of 94.14 is good. Factors inhibiting change are indicator targets that are not immediately changed, input at the end of the deadline, low competence, lack of PIC concern, and no satisfaction rating available on the e-Simdatin application. Supporting factors are the availability of SOPs, guidebooks, IT equipment, and leadership support. Efforts that should be made include changing targets on time, clarity in inputting output, socializing the use of the e-Simdatin application, fostering a sense of empathy for PICs, and adding features related to assessing user satisfaction of the e-Simdatin application. The suggestions given are based on data analysis and discussion to conclusions, namely providing research and education, clear and realistic time periods, supervision and monitoring, giving awards and evaluating activities.